Cannabinoid CB2 Receptors in a Mouse Model of Aβ Amyloidosis: Immunohistochemical Analysis and Suitability as a PET Biomarker of Neuroinflammation - Savonenko, Alena V.; Melnikova, Tatiana; Wang, Yuchuan; Ravert, Hayden; Gao, Yongjun; Koppel, Jeremy; Lee, Deidre; Pletnikova, Olga; Cho, Eugenia; Sayyida, Nuzhat; Hiatt, Andrew; Troncoso, Juan; et al. (PLOS ONE, 2015)
In Alzheimer’s disease (AD), one of the early responses to Aβ amyloidosis is recruitment of microglia to areas of new plaque. Microglial receptors such as cannabinoid receptor 2 (CB2) might be a suitable target for development of PET radiotracers that could serve as imaging biomarkers of Aβ-induced neuroinflammation. Mouse models of amyloidosis (J20APPswe/ind and APPswe/PS1ΔE9) were used to investigate the cellular distribution of CB2 receptors. Specificity of CB2 antibody (H60) was confirmed using J20APPswe/ind mice lacking CB2 receptors. APPswe/PS1ΔE9 mice were used in small animal PET with a CB2-targeting radiotracer, [11C]A836339. These studies revealed increased binding of [11C]A836339 in amyloid-bearing mice. Specificity of the PET signal was confirmed in a blockade study with a specific CB2 antagonist, AM630. Confocal microscopy revealed that CB2-receptor immunoreactivity was associated with astroglial (GFAP) and, predominantly, microglial (CD68) markers. CB2 receptors were observed, in particular, in microglial processes forming engulfment synapses with Aβ plaques. In contrast to glial cells, neuron (NeuN)-derived CB2 signal was equal between amyloid-bearing and control mice. The pattern of neuronal CB2 staining in amyloid-bearing mice was similar to that in human cases of AD. The data collected in this study indicate that Aβ amyloidosis without concomitant tau pathology is sufficient to activate CB2 receptors that are suitable as an imaging biomarker of neuroinflammation. The main source of enhanced CB2 PET binding in amyloid-bearing mice is increased CB2 immunoreactivity in activated microglia. The presence of CB2 immunoreactivity in neurons does not likely contribute to the enhanced CB2 PET signal in amyloid-bearing mice due to a lack of significant neuronal loss in this model. However, significant loss of neurons as seen at late stages of AD might decrease the CB2 PET signal due to loss of neuronally-derived CB2. Thus this study in mouse models of AD indicates that a CB2-specific radiotracer can be used as a biomarker of neuroinflammation in the early preclinical stages of AD, when no significant neuronal loss has yet developed.